2014
DOI: 10.1155/2014/325612
|View full text |Cite
|
Sign up to set email alerts
|

Deposition and Mineralogical Characteristics of Atmospheric Dust in relation to Land Use and Land Cover Change in Delhi (India)

Abstract: This study highlights that the increasing urbanization and industrialization in Delhi are responsible for higher fluxes of atmospheric dust and its chemical constituents. Delhi has experienced a drastic change in land use and land cover area during the past two decades. Road lengths of the city have increased by 76% from 1985 to 2011. The number of mobile vehicles has reached 80,52,508 in 2014 from 24,32,295 in 1994. The industrial units in Delhi have increased by 39.54% in 2011 as compared to 1994 value. Atmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…The chemical composition of the selected particles was determined using EDX, which revealed the presence of Silicon The microscopic examination revealed that the aerosol particles existed in several different geometries including 20 spherical, flat, agglomerate, irregular, cylindrical, crystal, ring, concave, chain and floccule; unlike the common assumption (spherical) in theory, but similar to those previously observed over different locations across the Indian region (Kumar et al, 2014;Pipal et al, 2014;Singh et al, 2014;Agnihotri et al, 2015;Tiwari et al, 2015;Pipal and Gursumeeran Satsangi, 2015;Mishra et al, 2015;Panda and Das, 2017). Such deviations of particles from spherical shape can alter the associated Single Scattering Albedo (SSA) (Mishra et al, 2015).…”
Section: Composition Retrievalsupporting
confidence: 68%
See 1 more Smart Citation
“…The chemical composition of the selected particles was determined using EDX, which revealed the presence of Silicon The microscopic examination revealed that the aerosol particles existed in several different geometries including 20 spherical, flat, agglomerate, irregular, cylindrical, crystal, ring, concave, chain and floccule; unlike the common assumption (spherical) in theory, but similar to those previously observed over different locations across the Indian region (Kumar et al, 2014;Pipal et al, 2014;Singh et al, 2014;Agnihotri et al, 2015;Tiwari et al, 2015;Pipal and Gursumeeran Satsangi, 2015;Mishra et al, 2015;Panda and Das, 2017). Such deviations of particles from spherical shape can alter the associated Single Scattering Albedo (SSA) (Mishra et al, 2015).…”
Section: Composition Retrievalsupporting
confidence: 68%
“…6). reported such a coating of Carbon on dust particles over the South Asian (Arimoto et al, 2006;Kumar et al, 2014) and the North-African (Deboudt et al, 2010) regions. Such a coating of carbonaceous species like BC on mineral dust would 'blacken' the dust and reduce its SSA making it more absorptive.…”
Section: Relationship Between Carbon Coating and Ambient Bc Mass Concmentioning
confidence: 91%
“…In addition, twenty-seven CNG buses were checked for meeting vehicular emission norms, of which twelve were low floor buses and fifteen were regular CNG buses (ibid., p. 73). Besides the monitoring of the vehicular pollution, the CPCB also conducted a study in 2014 to analyse the dust fall rates in Delhi, and while the dust fall rates are dependent on spatial and meteorological factors such as temperature, wind movement, etc., the deposition flux, that is, amount of dust per square meter per annum, for Delhi was found to be 35.28 according to the study (Kumar, Verma, & Kulshreshtha, 2014). The study concluded that decreasing green area and increasing residential and commercial built-up space contribute to high fluxes of dust fall in Delhi.…”
Section: Assessment and Monitoring Of Vehicular Pollutionmentioning
confidence: 86%
“…Delhi has an annual average dustfall of 35 g/m 2 /yr with some of the sites showing figures as high as 168 g/m 2 /yr. 38 For comparison, residential areas adjacent to Jharia coal mines in Jharkhand have an average dustfall of 116.6 g/m 2 /yr. 39 Dust affects the urban environment especially air pollution, to which it is a major contributor.…”
Section: How Cities Contribute To Climate Changementioning
confidence: 99%